2020
DOI: 10.1016/j.seppur.2019.115915
|View full text |Cite
|
Sign up to set email alerts
|

Core/shell FeVO4@BiOCl heterojunction as a durable heterogeneous Fenton catalyst for the efficient sonophotocatalytic degradation of p-nitrophenol

Abstract: In this study, a FeVO4@BiOCl p-n heterojunction with n-type porous FeVO4 nanorods as the core and p-type flower-like BiOCl nanostructures as the shell was successfully prepared by a facile hydrothermal method. The novel heterostructure was investigated as a durable heterogeneous Fenton catalyst for ultrasonic irradiation (US), ultraviolet irradiation (UV) and coupling irradiation systems (US/UV). Characterization of FeVO4@BiOCl core shell heterojunction was conducted by XRD, SEM, EDS elemental mapping, TEM, HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(15 citation statements)
references
References 92 publications
2
13
0
Order By: Relevance
“…The comparison of catalytic dosage, sonication time and removal efficiency of proposed catalyst and reported catalysts for the degradation of nitrophenol compounds was presented in Table 1. As can be seen, the proposed catalyst displayed relatively short sonication time and also considerable removal efficiency comparing with other reported catalysts [22][23][24]45,46]. The results reported in this study showed that the prepared catalyst is a potential candidate for the removal of PNP from aqueous solution.…”
Section: Comparison With Other Reported Heterogeneous Sono-fenton Catalystssupporting
confidence: 50%
“…The comparison of catalytic dosage, sonication time and removal efficiency of proposed catalyst and reported catalysts for the degradation of nitrophenol compounds was presented in Table 1. As can be seen, the proposed catalyst displayed relatively short sonication time and also considerable removal efficiency comparing with other reported catalysts [22][23][24]45,46]. The results reported in this study showed that the prepared catalyst is a potential candidate for the removal of PNP from aqueous solution.…”
Section: Comparison With Other Reported Heterogeneous Sono-fenton Catalystssupporting
confidence: 50%
“…Previous studies also confirmed that ˙OH played an important role in degrading various dyes such as acid blue 113, acid blue 7 and methyl orange using US/UV/ZnO/PS, 11 US/metal–organic framework‐2/peroxydisulfate and formic acid/UV systems, respectively 41,42 . Other reactive species such as h+ and electrons (e − ) may exist in the current system, but their contributions to dye removal were reported to be small in comparison with the ˙OH 43 …”
Section: Resultsmentioning
confidence: 60%
“…According to previous research, BiOCl-based photocatalysts can be divided into three main categories: metal/BiOCl, semiconductor/BiOCl, and carbon/BiOCl heterogeneous structures. ,,,, ...…”
Section: Categories Of Biocl-based Photocatalystsmentioning
confidence: 99%
“…The synthesis of type-II and Z-scheme junctions in metal oxide (sulfide)/BiOCl systems is a promising method to acquire higher photocatalytic performances, which provides a better opportunity to understand the transfer pathways of photoinduced charge carriers and further reveals the photocatalytic mechanisms. In recent years, the controllable synthesis of metal oxide (sulfide)/BiOCl and other oxysalts/BiOCl photocatalysts has been extensively reported, and the relationships between structure and property as well as performance of products have also been amply elucidated. …”
Section: Categories Of Biocl-based Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation